Distant Sons : a novel - Johnston, Tim, 1962- (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2023)
"The actions of two young working men with secrets ignite the passions and violence of a small Wisconsin town still haunted by the unsolved disappearance of three boys in the 1970s"--.
new book 2023 fall.
Keywords: Suspense fiction; Mystery and detective stories; Novels